Dexmedetomidine Administration does not Affect Electrocorticography Reading during Epilepsy Focal Removal Surgery - Nauli, Anggarian Oloan; Harahap, M Sofyan (Jurnal Neuroanestesi Indonesia, 2024)
Epilepsy prevalent across all ages and genders, making it one of the most widespread neurologic disorder. Worldwide, 20-40% of epilepsy patients are refractory or resistant to oral anti-epileptic drugs, requiring surgery to treat their seizures. The use of electrocorticography (ECoG) can help determine the focus of epilepsy and requires anaesthetic drugs that do not affect the electroencephalography (EEG) readings during surgery. The aim of this case was to study the effect of using dexmedetomidine (DEX) as additional to maintenance anesthesia in epileptic craniotomy surgery with ECoG. A 28-year-old man came to the hospital with complaints of recurrent seizures, generalized tonic-clonic type seizures that lasted 2-3 minutes, was unconscious during the seizure, fell asleep afterwards, and recurred 2-3 times a day. The patient had suffered from epilepsy since 4 years ago. Physical and supporting examinations were within normal limits. Head MSCT examination with contrast suspected oligodendroglioma. The patient was administered dexmetomidine while underwent epilepsy craniotomy surgery with ECoG to remove the tumor which was suspected to be the epileptic focus. The choice of anesthetic agent in epilepsy craniotomy, especially when involving ECoG modalities, requires special consideration to improve intraoperative quality and postoperative outcomes. Propofol is the most widely used induction agent. However, these agents have anticonvulsant effects and activate non-specific spike waves in large areas of the brain. This has the potential to interfere with spike wave monitoring with ECoG. The use of dexmedetomidine has been shown to produce a stable hemodynamic effect and does not affect the ECoG readings. The use of DEX as an adjuvant in anesthesia maintenance does not inhibit spike waves during surgery, so ECoG can be used effectively for anesthesia in craniotomy operations with ECoG